2013
DOI: 10.1074/jbc.m112.418830
|View full text |Cite
|
Sign up to set email alerts
|

The Intermediate Filament Vimentin Mediates MicroRNA miR-378 Function in Cellular Self-renewal by Regulating the Expression of the Sox2 Transcription Factor

Abstract: Background:We have previously demonstrated that miR-378 expression promotes tumorigenesis and angiogenesis. Results: We show here that miR-378 plays roles in cell self-renewal, survival, and colony formation by enhancing Sox2 expression through repressing vimentin level. Conclusion: Our study demonstrates that miR-378 can trigger a signal cascade. Significance: Our study reveals a novel signaling pathway in modulating cell stemness by miR-378 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…A similar phenotype was also observed when miR-378 was overexpressed in chronic myeloid leukemia K562 cells [23]. The over-expression of miR-378 in a human primary glioblastoma cell line promoted a stem cell phenotype with an increase in proliferation, adipogeneic differentiation, and colony formation [24]. These observations align with the loss in proliferation potential (see Supplemental Table S2) and corresponding loss in miR-378 expression that we observe as ASC are cultured over time.…”
Section: Discussionsupporting
confidence: 84%
“…A similar phenotype was also observed when miR-378 was overexpressed in chronic myeloid leukemia K562 cells [23]. The over-expression of miR-378 in a human primary glioblastoma cell line promoted a stem cell phenotype with an increase in proliferation, adipogeneic differentiation, and colony formation [24]. These observations align with the loss in proliferation potential (see Supplemental Table S2) and corresponding loss in miR-378 expression that we observe as ASC are cultured over time.…”
Section: Discussionsupporting
confidence: 84%
“…miR-378 is involved in promoting cell survival, tumor growth, and angiogenesis in glioblastoma cells [26], in regulating osteoblast differentiation [28] and in tumor cell self-renewal and chemoresistance [27]. However, the function of miR-378 in liver cancer cells has not been reported thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that miR-378 enhanced liver cancer cell proliferation, migration, invasion and metastasis. In addition to these functions, miR-378 also participates in cellular self-renewal [27] and osteoblast differentiation regulation [28]. Thus, considering its biological characteristics, miR-378 is categorized as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With one notable exception, SOX2-targeting miRs are associated with downregulation of SOX2. However, Deng et al reported that miR-378 increases SOX2 expression in breast cancer [ 154 ]. Although the types of breast cancer specimens examined were not described, they noted miR-378 was expressed at higher levels in breast tumor tissue than adjacent non-tumorigenic tissue.…”
Section: Regulation Of Sox2 Expressionmentioning
confidence: 99%